ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAPORAN BISNIS MELAUI INTERNET ( INTERNET BUSINESS REPORTING ) PADA WEBSITE PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Setyo Slamet Riyadi Slamet Riyadi; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
The rapid growing of the internet creates a new way for the companies to disseminate their business informations in better quality,low costs, and can reach the wider users. Although the Internet provides some benefits in corporate disclosure practice, not all companies presenting their business informations on the internet. In other words, there are various factors that influence the practice of internet business reporting (IBR). This study aims to examine the potential factors that may affect the level of IBR. Such as firm size, profitability, listing age, auditor type, industry type, foreign-listing status, and competition of industry.Internet Business Quality Index (IBRQ Index) is used to measure the level of  internet business reporting on the Indonesian listed companies. By using purposive  sampling methods, 259 companies were chosen. Multiple regression analysis is used to examine the determinants of the internet reporting, the results show that firm size and foreign-listing status positively and significantly influences to IBR; profitabilitiy, auditor type and industry type positively and unsignificantly influences to IBR; listing age negatively and significantly influences to IBR;competition of industry negatively and unsignificantly influences to IBR.